Validity and reliability the Meaning in Life Questionnaire (MLQ) ; Men who have sex with men at West Sumatera Indonesia - Yafi Sabila Rosyad; Hema Malini; Rika Sarfika (Riset Informasi Kesehatan, 2019)
The meaning of life is the meaning of every event that occurs both pleasant and painful. Meaning of life of each individual is very unique and different from each other. The meaning of life questionnaire (MLQ) is a questionnaire measuring the meaning of life developed by Steger by deviding into two sub items present and search each consisting of five questions. The purpose of this article is to perform the validity and reliability of the meaning in life questionnaires (MLQ) Indonesian version. The respondents of this study are 50 persons men who have sex with men seropositive HIV in NGOs Saiyo Sakato Bukit Tinggi and NGOs Teratak Jiwa Hati West Sumatera. Validity and reliability testing is done by reliability scale analysis technique. The question item validity is seen from the magnitude of r-table value with r-count and reliability seen through Cronbach's alpha coefficiency. The results of this study show the meaning in life questionnaire (MLQ) in the context of Indonesian all items of valid and reliable.